Answer:
The answer is 4:
2+2 =4
Step-by-step explanation:
Hi how are you?
Answer:
A: ![6x^2(x^8-16)](https://tex.z-dn.net/?f=6x%5E2%28x%5E8-16%29)
B: ![6x^2(x^4+4)(x^2+2)(x^2-2)](https://tex.z-dn.net/?f=6x%5E2%28x%5E4%2B4%29%28x%5E2%2B2%29%28x%5E2-2%29)
Step-by-step explanation:
<u>A:</u>
Our expression is
. We need to find some common factors. Clearly, we can see that both terms share the x² part, so we can definitely take that out:
![6x^{10}-96x^2](https://tex.z-dn.net/?f=6x%5E%7B10%7D-96x%5E2)
![x^2(6x^8-96)](https://tex.z-dn.net/?f=x%5E2%286x%5E8-96%29)
Let's see if 96 is divisible by 6:
96 ÷ 6 = 16; since there's no remainder / the remainder is 0, we know 96 is divisible by 6, so we can also factor out 6:
![x^2(6x^8-96)](https://tex.z-dn.net/?f=x%5E2%286x%5E8-96%29)
![6x^2(x^8-16)](https://tex.z-dn.net/?f=6x%5E2%28x%5E8-16%29)
Thus, the answer to part A is
.
<u>B:</u>
Look at the
part of the above factored expression. Notice that it is a difference of squares (because
and 16 = 4²), so we can write this as:
![x^8-16](https://tex.z-dn.net/?f=x%5E8-16)
![(x^4+4)(x^4-4)](https://tex.z-dn.net/?f=%28x%5E4%2B4%29%28x%5E4-4%29)
Now take a look at the
part. Again, it's a difference of squares because
and 4 = 2², so rewrite that as:
![x^4-4](https://tex.z-dn.net/?f=x%5E4-4)
![(x^2+2)(x^2-2)](https://tex.z-dn.net/?f=%28x%5E2%2B2%29%28x%5E2-2%29)
Put it all together:
![6x^2(x^4+4)(x^2+2)(x^2-2)](https://tex.z-dn.net/?f=6x%5E2%28x%5E4%2B4%29%28x%5E2%2B2%29%28x%5E2-2%29)
Thus, the answer to part B is
.
Answer:
![48\pi](https://tex.z-dn.net/?f=48%5Cpi)
Step-by-step explanation:
Volume =
![r ^{2} \times \pi \times h = 4 ^{2} \times \pi \times 3 = 48\pi](https://tex.z-dn.net/?f=r%20%5E%7B2%7D%20%20%5Ctimes%20%5Cpi%20%5Ctimes%20h%20%3D%204%20%5E%7B2%7D%20%20%5Ctimes%20%5Cpi%20%5Ctimes%203%20%3D%2048%5Cpi)
r=4
h=3
Answer:
8/1
Step-by-step explanation:
To find slope you would do:
rise/run
Up and down is the rise
Left and right is the run
In your problem it goes up 8 and right 1
Answer:
<em>y = (x - 4)² - 4 </em>
Step-by-step explanation:
y = x² - 8x + 12
y = ( x² - 2(4)x + 4² ) - 4² + 12
<em>y = (x - 4)² - 4</em>